Hubungan Peran Kelompok Teman Sebaya dengan Perilaku Bullying pada Anak - Maharani, Ni Putu Ananda; Sukmandari, Ni Made Ari; Laksmi, Ida Ayu Agung (Jurnal Gema Keperawatan, 2025)
School is a place for children to learn and gain knowledge, and help shape positive character in children until adulthood. In reality, lately there have been frequent acts of violence, both by teachers against students, and by fellow students. The violence can be in the form of physical violence and psychological violence. The phenomenon of bullying is often heard in all aspects of life, one of which is in educational institutions such as schools. The many cases of violence in schools cause problems that occur in the school environment. Peers are at high risk of causing bullying behavior in children, where children often spend time socializing and interacting with peers compared to family. The results of the report obtained from the principal of an elementary school in Badung Regency showed that there were 40 cases of bullying behavior from January 3, 2022 to October 2022. The purpose of this study was to determine the relationship between the role of peer groups and bullying behavior in children at SD Negeri 4 Lukluk. This study uses a quantitative method using a descriptive correlation research design with a cross-sectional approach. The sampling technique in this study used a nonprobability sampling technique with a total sampling method with a sample size of 72 respondents. Data analysis using spearman-rank to determine the relationship between the role of peer groups and attachment variables, namely bullying behavior. The results of the study showed a relationship between the role of peer groups and bullying behavior in children of SD Negeri 4 Lukluk.